Avaliação da influência do plasma rico em plaquetas, da terapia com laser em baixa intensidade ou da associação de ambos na cicatrização de defeitos de fenestração periodontal em ratos: estudo histoquímico e imunoistoquímico - Neves, Adrieli de Paula [UNESP] (2015)
This study histochemically and imunoistochemically evaluated the influence of platelet-rich plasma (PRP), low-level laser therapy (LLLT), or their combination on the healing of periodontal fenestration defects (PFD) in rats. PFD were surgically created in the mandible of 80 rats. The animals were randomly divided into 4 groups: 1) C (Control) and 2) PRP - defects were filled with blood clot or PRP, respectively; 3) LLLT and 4) PRP/LLLT - defects received laser irradiation, were filled with blood clot or PRP, respectively, and then irradiated again. Animals were euthanized at either 10 or 30 days post-operative. Immature and mature collagen fibers were histochemically evaluated and their percentages were calculated. Runtrelated transcription factor 2 (Runx2), osteocalcin (OCN), osteopontin (OPN) and alkaline phosphatase (ALP) immunohistochemical staining were performed. Runx2-positive cells were quantified. A semi-quantitative method was used to evaluate OCN, OPN, and ALP immunolabeling pattern. Data were statistically analyzed. Statistically significant differences were not observed in the percentages of immature and mature collagen fibers when each experimental group was compared to control. At 10 days, PRP and PRP/LLLT groups presented a significantly higher number of Runx2-positive cells than control; PRP/LLLT presented significantly higher OCN and OPN immunolabeling than control; and statistically significant differences were not observed in the ALP immunolabeling. At 30 days, statistically significant differences were not observed in the OCN, OPN and ALP immunolabeling among the experimental groups...